The Intersection of Language Modeling, Child Development, and Computational Thinking in Elementary School Education: A Framework for Enhancing 21st-Century Skills - Ferril Irham Muzaki; Adi Atmoko; Anang Santoso; Ade Eka Anggraini (The Bioscan, 2025)
In the rapidly making circumstance of 21st-century setting up, the set out some reasonable set out some reasonable compromise of language depicting, kid improvement, and computational thinking has emerged as an unprecedented technique for controlling early age school bearing. This study analyzes how these three spaces meet to shape the psychological, etymological, and socio-significant improvement of energized understudies. Language having a tendency to, spread out in computational semantics, mirrors the customary events of language getting, offering educators imaginative contraptions as far as possible and social endpoints. Computational thinking, a convincing reasoning design that loads rot, plan interest, and algorithmic thinking, draws in trustworthy reasoning and creative mind. Together, these spaces make a synergistic improvement that stays aware of the improvement of major 21st-century limits, including created course, thinking limits, and mechanized shared brand name. This paper mixes existing evaluation, consolidates the exchange between these makes, and proposes enlightening techniques for orchestrating them into grade school informational exercises. By moving past language, understanding, and improvement, this approach prepares students to survey the complexities of a mechanized world while making solid learning and adaptability.